2010
DOI: 10.1021/am100687n
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxides for Homogeneous Dispersion of Carbon Nanotubes

Abstract: Graphene oxides (GOs) in terms of both structure and property are essentially polyelectrolytes in a two-dimensional sheet configuration. As is well-established in the literature, polyelectrolytes are, in general, good dispersion agents for single-walled carbon nanotubes (SWNTs), which are otherwise in bundles because of strong van der Waals interactions. We report here a study in which GOs were used to disperse SWNTs, both as-purified and separated semiconducting SWNTs, for solution-like homogeneous suspension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(82 citation statements)
references
References 43 publications
5
75
1
Order By: Relevance
“…MWNTs show a narrower D band, which may be due to the higher ordered structure of nanotubes compared with the fragmented GO. The 2D band of GO/MWNTs and LAA-rGO/MWNTs composites is attributed to the MWNTs, as there is no absorption for GO at the high excitation wavelength [12]. In addition, the D and G band peak shapes of GO/MWNTs and LAA-rGO/MWNTs were dominated by MWNTs, as evidenced by the narrower D band peak compared to GO and LAA-rGO, and similar G band peak shape to MWNTs [12].…”
Section: Reduction Of Go and Go/mwnts Dispersions And Characterizationmentioning
confidence: 93%
See 2 more Smart Citations
“…MWNTs show a narrower D band, which may be due to the higher ordered structure of nanotubes compared with the fragmented GO. The 2D band of GO/MWNTs and LAA-rGO/MWNTs composites is attributed to the MWNTs, as there is no absorption for GO at the high excitation wavelength [12]. In addition, the D and G band peak shapes of GO/MWNTs and LAA-rGO/MWNTs were dominated by MWNTs, as evidenced by the narrower D band peak compared to GO and LAA-rGO, and similar G band peak shape to MWNTs [12].…”
Section: Reduction Of Go and Go/mwnts Dispersions And Characterizationmentioning
confidence: 93%
“…The 2D band of GO/MWNTs and LAA-rGO/MWNTs composites is attributed to the MWNTs, as there is no absorption for GO at the high excitation wavelength [12]. In addition, the D and G band peak shapes of GO/MWNTs and LAA-rGO/MWNTs were dominated by MWNTs, as evidenced by the narrower D band peak compared to GO and LAA-rGO, and similar G band peak shape to MWNTs [12]. However, the G band peaks of GO/MWNTs and LAA-rGO/MWNTs at all conditions seem to show splitting into two peaks due to the presence of two species; i.e., GO and MWNTs or rGO and MWNTs.…”
Section: Reduction Of Go and Go/mwnts Dispersions And Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, surface modification can impair their inherently unique properties, thus affecting the end-use performance, although the aqueous dispersion was greatly improved (Zhang et al 2010). Fortunately, graphene oxide (GO) used as a novel dispersant in aqueous system may solve the above mentioned problem (Tian et al 2010). GO, a two-dimensional (2D) and one-atomic-thick sp 2 carbon layer exfoliated from graphite, shares many similar properties to CNTs ).…”
Section: Introductionmentioning
confidence: 99%
“…To solve the issue of intrinsic insolubility of CNTs in water, GO with high solubility has been introduced as surfactant to disperse CNTs through strong π-π stacking interaction [165][166][167]. Dong et al [157] have experimentally demonstrated the spontaneous formation of SWCNT/ GO core-shell structure.…”
Section: Go/rgo Combined With Other Carbon Materialsmentioning
confidence: 99%